PUNGGAWA-SAWI VALUES EDUCATION IN OVERSEAS BUGIS ETHNIC FAMILY AS LOCAL WISDOM OF THE FISHERMAN COMMUNITY (DESCRIPTION ANALYSIS FISHERMAN SOCIETY ON COAST BANDAR LAMPUNG) - Irawan, Rudi (International Journal of Ethno-Sciences and Education Research, 2022)
In changes the values of life skills that occur in the Bugis ethnic fishing community, Karang Village, Telukbetung Timur District, Bandar Lampung City as local wisdom are due to incompatibility between the rules that are lived by the behavior they carry out, the weak role of social institutions in conducting supervision and socialization.  The values of life that are framed in the activities of Bagang in the next generation are low in interest and the next generation to apply the values of life of the Bugis ethnic in overseas lands in their interactions among family members, the community as well as in the development and implementation of the Bagang activity.  This study aims to determine the description of local wisdom in the process of educating the value of the life of the Bagang fishing community (read; Bagan) of the Overseas Bugis ethnicity in Karang Village, Teluk Betung Timur District, Bandar Lampung City. The method used in this research is descriptive analytical research with a qualitative approach that functions to describe and explain a complex reality by applying concepts and theories that have been developed by scientists.Based on the results of the research and analysis, it was found that (1) the pattern of punggawa fishermen's families in preserving local wisdom in overseas lands by inculcating life skills values was more likely to be participatory education patterns.  This pattern tends to emphasize the process of the child's association with other punggawa or sawi who are more mature in developing their potential by providing maximum opportunities for achieving independence in living their lives.  (2) The sawi family in the process of preserving local wisdom by instilling life skills values their education, tends to use a repressive pattern from older family members to younger family members, either directly or indirectly.  Consequently, those with low education are positioned as people who accept the values of local wisdom in the lower class social strata.  (3) The process of applying the life skills values of punggawa or sawi  as local wisdom in the Bagang fishing community of the overseas Bugis ethnic in the Karang City Village area occurs because of the community's desire to survive with their existence as a fishing community that is unique with its traditions.